ACUTE EFFECTS OF WHOLE BODY VIBRATION TRAINING ON THE RANGE OF MOVEMENT AND THE MUSCULAR FUNCTION OF THE LOWER LIMBS OF THE SOCCER PLAYER - Fuad Babajic; Edin Užičanin; Erol Kovačević (Sport Scientific And Practical Aspects, 2025)
The basic aim of this study was to determine the acute effects whole body vibration training applied in static stretching exercises, on the range of movement and the muscular function of the lower extremities in the soccer players. For this purpose, footballers (N = 34) were engaged, chronologically aged 20-24. The vibration (experimental) protocol (VSI) implied the practice of static stretching performed on the included vibrational platform (f = 40 Hz, A = 2 mm), while the standard protocol (SSI) implied performing the same exercises but with the vibration platform off. The results of the t-test demonstrated that the vibration protocol (VSI) can contribute to a significant (acute) improvement lower extremity passive range of motion compared to the standard (SSI) protocol. However, there were no statistically significant differences between the applied protocols (SSI and VSI) on the variables for the assessment of muscular function (vertical jumps and sprints). The results of this study indicate that the whole body vibration training applied in static stretching exercises effectively improves the range of movement of lower limbs, but not the muscular function measured by the types of vertical jump and maximum sprint test, in acute settings